1995
DOI: 10.1002/hep.1840210239
|View full text |Cite
|
Sign up to set email alerts
|

Increased sinusoidal wall permeability and liver fatty change after two-thirds hepatectomy: An ultrastructural study in the rat

Abstract: Accumulation of lipids in the hepatocyte cytoplasm after partial hepatectomy (PH) has long been recognized, but the mechanism behind this phenomenon is still poorly understood. In this study, rats subjected to a standard two-thirds PH showed early and marked increase in portal venous pressure (P < .01). On scanning electron microscopy, the regenerating liver fixed by portal perfusion under hemodynamic conditions identical to that found in vivo during the first 24 hours showed a significant (P < .01) 10-fold in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Inclusion of "gaps"-those pores larger than 300 m in diameter-as fenestrae could skew the mean diameter to the larger size, especially if there are more "gaps" in zone 1 than zone 3. Our mean porosity measurements also vary from previously published reports, 11,23 but otherwise correlate well in that porosity is greater in zone 3 than in zone 1. 9,23 Previous work has suggested that direction of perfusion, either anterograde or retrograde to inherent blood flow, can influence fenestration size.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Inclusion of "gaps"-those pores larger than 300 m in diameter-as fenestrae could skew the mean diameter to the larger size, especially if there are more "gaps" in zone 1 than zone 3. Our mean porosity measurements also vary from previously published reports, 11,23 but otherwise correlate well in that porosity is greater in zone 3 than in zone 1. 9,23 Previous work has suggested that direction of perfusion, either anterograde or retrograde to inherent blood flow, can influence fenestration size.…”
Section: Discussionsupporting
confidence: 85%
“…This correlation has been shown previously as a general phenomenon in the midlobular region of the sinusoid within 24 hours of resection. 11 Here, we report that a gradient of lipid deposition is spatially and temporally related to the increased fenestration size along the portal-central axis. Under conditions of increased fenestration size in zone 1, chylomicron remnants are not excluded from hepatocytes by the SEC.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Variation in the selection of sinusoids for micrographs, image analysis of artefacts, and measurement of cell area for porosity and fenestration frequency have led to major discrepancies in published results. A standardized approach for evaluation and measurement of fenestrations and the minimum requirements for data presentation have not been clearly addressed in the literature previously 4,10,[20][21][22][23][24][25][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%